Pengaruh Keterampilan Komunikasi Orang Tua terhadap Kepercayaan Diri Anak TK di TK Negeri Harapan - Felista Mohamad; Elva M. Sumirat; Naswa Ramadani Mamonto; Putri Regina Sinubu; Mega Putri Ramadani; Siti Fadila; Amaliatul Khairah Latif; Revalina Mokoagow (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This study aims to analyze the influence of parental communication skills on the self-confidence of kindergarten children using a quantitative approach. The background of this research is rooted in the essential role of effective parental communication in shaping the psychosocial development of children, particularly in fostering self-confidence, which is crucial for children's social and academic success. The research sample consisted of parents and kindergarten children selected through purposive sampling. Data were collected using questionnaires designed to measure parental communication patterns and children's levels of self-confidence. Data analysis involved descriptive and inferential statistics, including simple linear regression to examine the relationship and effect of parental communication skills on children's self-confidence. The results reveal that positive, supportive communication skills characterized by democratic communication patterns have a significant positive effect on increasing children's self-confidence. Effective and empathetic communication creates a conducive environment for children to express themselves, boosting their self-esteem and social-emotional potential. The study concludes that enhancing parental communication skills is a vital strategy for family guidance and early childhood education to optimally support the development of children's self-confidence.